Mengapa Sepak Bola Menjadi Populer di Kalangan Siswa Sekolah Dasar? - Mulyana, Agus; Shafira, Diva; Aditya, Ferdino Arief; Anggia, Intan Ratu; Haq, Mohamad Arinal; Daud, Muhammada Rafi Bahiruddin; Putri, Nasya Nurlillah Kusuma; Ardhiyansah, Saiful (Indo-MathEdu Intellectuals Journal, 2024)
This article aims to identify and analyze the factors that cause elementary school children's interest in football to increase. This study uses a qualitative approach with a literature review method. The data collection process is carried out through scientific journals, books, and research reports that focus on research. The search was conducted through academic databases such as Google Scholar, PubMed, and other online journal portals Using relevant keywords such as "popularity of elementary school football", "influence of media on elementary school children", "early childhood football coaching", and "social aspects of children's football". Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the analysis showed that media influence, such as games aired on television or soccer content that went viral on social media platforms, gave elementary school children greater access to the sport. Coaching from an early age, both through school programs and local football clubs, provides opportunities for children to start learning and loving the sport from an early age. In addition, social aspects such as peer relationships and the experience of playing in a team can increase elementary school children's interest in football, as this sport not only provides an opportunity to play, but also strengthens the social bonds between them